ROLE OF SIMPLIFIED ADMISSION CRITERIA FOR PREDICTING SEVERE COMPLICATIONS OF GALL STONE PANCREATITIS - Shah, Azhar; Haq, Faheem ul; Ullah, Anayat; Rehman, Riaz Ur (Journal of Ayub Medical College Abbottabad, 2010)
Background: Gallstone Pancreatitis (GP) is not an uncommon disease in our country and is associated with large number of morbidity and mortality especially if severe complications develop. Different criteria have been developed to predict the complications of GP. Simple admission criteria are better predictors of severe complications of GP than an APACHE II score of 5 or greater, a modified Imrie (Glasgow) score of 3 or greater, and a Biliary Ranson score of 3 or greater. The purpose of this study was to determine the role of simplified admission criteria in predicting severe complications of Gallstone Pancreatitis. Methods: This was a descriptive study conducted in Surgical ’˜A’ Unit, Khyber Teaching Hospital Peshawar between July 16th 2007 to November 30th 2008. Total 52 patients (42 women and 10 men, aged range from 18 to 76 years, with mean age, 39 years) who presented to our unit with gallstone pancreatitis were included in the study through technique of non-probability convenient sampling. The main outcome measures were major local and systemic complications requiring intensive care unit care, and death. Physiologicalfactors and laboratory data were collected on admission and recorded daily. Results: Seven patients (14%) had severe complications with mortality of 2%. On univariate analysis, a white blood cell count of 14500/dL or more (p=0.03), a serum glucose level of or more ‰¥150 mg/dL (8.3 mmol/L) (p<0.001), anAPACHE II score of 5 or greater (p=0.008), a modified Imrie score of 3 or greater (p<0.001), and a biliary Ranson score of 3 or greater (p=0.03) were statistically associated with the development of severe complications. On multivariate analysis, only a serum glucose level of ‰¥150 mg/dL or more (8.3 mmol/L) was predictive of adverse events (p<0.001). Conclusions: Glucose level (‰¥150 mg/dL) is the best single admission predictor of severe complications of Gallstone Pancreatitis and is superior to an APACHE II score of 5 or greater, a modified Imrie score of 3 or greater, anda biliary Ranson score of 3 or greater. Keywords: Gallstones pancreatitis, admission criteria, complications